The Influence of Pedagogical Competence and Personal Competence on Teachers’ Professional Competence, with Organizational Culture as a Mediating Variable - Esih Sukaesih; Atikah Atikah; Dede Ibnu Romdoni; Hamidah Hamidah; Mutoharoh Mutoharoh (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
National education quality is fundamentally shaped by teachers' professionalism as the frontline of the learning process. This study aims to examine the influence of pedagogical competence and personality competence on teachers' professional competence, and to investigate the mediating role of organizational culture within that relationship. A quantitative approach with a causal research design was employed, applying total sampling to 30 teachers as respondents. Data were gathered through Likert-scale questionnaires and analyzed using path analysis and the Sobel test. The findings reveal that pedagogical competence (β=0.318) and personality competence (β=0.287) each exert a positive and significant influence on professional competence. Organizational culture demonstrated the strongest predictive coefficient (β=0.389). The Sobel test confirmed that organizational culture functions as a partial mediator in both relationships. The model accounts for 72.4% of the variance in professional competence. It is concluded that strengthening foundational teacher competencies must be accompanied by the sustained development of a conducive organizational culture